AN ECOSYSTEM SERVICE-BASED APPROACH TO DESIGN AGRI- ENVIRONMENT-CLIMATE PAYMENTS FOR THE RURAL DEVELOPMENT PROGRAMS 2014-2020. THE CASE OF THE AUTONOMOUS PROVINCE OF TRENTO - La Notte, A.; Scolozzi, R.; Molfetta, P.; Gubert, F.; Molignoni, R.; Franchi, R.; Pecile, A. (Annali di Botanica, 2014)
The justification for measures addressing Agri- Environment-Climate payments (AEC) is a crucial issue for authorities working at the Rural Development Program (RDP). The RDP 2014-2020 offers the possibility to include environmental benefits and externalities as elements that drive decision-making. Such benefits and externalities include the ecosystem services (ES) provided by farming practices in semi-natural ecosystems such as alpine pastures and mountain hay meadows. An approach based on ES is proposed to support and to account for AEC measures in the Autonomous Province of Trento, relying on decision models and scenario analysis. The method is still in development and is currently being tested as to its effectiveness. In the present paper, however, we present the approach and the case study area, with preliminary insights and expected results. The decision framework consists of livestock management and alpine grassland use; its objective is the sustainable production of fodder, compatible with conservation of grassland biodiversity. In addition to habitat for biodiversity, other ES such as water purification, aesthetic and recreation value will be considered in subsequent steps. The need for simplification and reliability, along with data scarcity, strongly limits the degree of sophistication and makes it challanging to create a tool, which is accurate and easy-to-use at the same time.